Constructing the Epiphany: Joycean Approach to Selected Stories from Dubliners - Paudel, Shiv Raj; Dahal, Babu Ram (Janajyoti Journal, 2024)
By using the Joycean lens in the construction of epiphany in some selected stories from Dubliners, James Joyce tries to uncover how tactfully he examines inner lives of his characters and their socio-cultural environment. By emphasizing on simple ordinary events Joyce finds extraordinary within the mundane offering deep insights into the characters of the stories in Dubliners. With regard to use of epiphany in the selected stories of the book Dubliners, the present study tries to investigate how James Joyce adopted the literary device of "epiphany" in Dubliners. It is argued that Joycean style of developing the epiphanic moment is accomplished through the mode of character transformation, especially among his protagonists. Through the potent use of symbolic characters, Joyce conveys a realistic reflection of Dubliners as a "Living dead" against the backdrop of the contemporary impact of modern developments in Irish society and their consequent implications of cultural, spiritual, and moral paralysis. The main characters in the chosen stories experience a psychological transformation from the private to the public, egoistic to social, ideal to real, childhood to adolescent, and ignorance to knowledge, which causes them to lose faith in the true nature of the universe they live in. Joycean epiphanies are more spiritual than those that result from outside forces. The concept of a Bildungsroman will be used in the study as a theoretical technique that focuses on the development and coming-of-age experiences of the main characters. It will also be used to analyze the conclusions that the psychological change of the characters is what drives Joyce's building of epiphany.